2015
DOI: 10.1016/j.physletb.2015.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Hypernuclear production cross section in the reaction of 6Li + 12C at 2 A GeV

Abstract: Hypernuclear production cross sections have been deduced for the first time with induced reaction of heavy ion beam on fixed target and by means of the invariant mass method by the HypHI Collaboration exploiting the reaction of 6 Li + 12 C at 2 A GeV or √ s N N = 2.70 GeV. A production cross section of 3.9 ± 1.4 μb for 3 H and of 3.1 ± 1.0 μb for 4 H respectively in the projectile rapidity region was inferred as well as the total production cross section of the hyperon was measured and found to be equal to 1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 49 publications
(57 reference statements)
2
53
0
Order By: Relevance
“…The study of cluster and hypernucleus production, which reflects the phase space density during the expansion phase, is of particular interest from experimental as well as from theoretical side. Experimentally clusters have been observed at all energies: from low energiesmeasured by ALADIN [6,7], INDRA [8], FOPI [9], Hy-pHI [10] Collaborations, to (ultra-) relativistic energiesmeasured by NA49 [11], STAR [12,13], ALICE [14][15][16] Collaborations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of cluster and hypernucleus production, which reflects the phase space density during the expansion phase, is of particular interest from experimental as well as from theoretical side. Experimentally clusters have been observed at all energies: from low energiesmeasured by ALADIN [6,7], INDRA [8], FOPI [9], Hy-pHI [10] Collaborations, to (ultra-) relativistic energiesmeasured by NA49 [11], STAR [12,13], ALICE [14][15][16] Collaborations).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24]. Recent experimental results [10,13,15] have shown that hypernuclei and anti-hypernuclei can be formed in heavy-ion collisions from SIS to LHC energies. Detailed theoretical calculations have identified two sources of hypernuclei in these reactions: In the overlap region of target and projectile, hyperons are produced in energetic first chance NN collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the analyses are given in [11]. A production cross section of 3.9 ± 1.4 µb for 3 Λ H and of 3.1 ± 1.0 µb for 4 Λ H respectively in the projectile rapidity region was deduced as well as the total production cross section of the Λ hyperon measured to be 1.7 ± 0.8 mb.…”
Section: The Likelihood Functionmentioning
confidence: 99%
“…σ sys and σ prior stand for the systematic uncertainties and the prior sensitivity uncertainties. The table is taken from [11].…”
Section: The Likelihood Functionmentioning
confidence: 99%
See 1 more Smart Citation